Tactile Reflex Development Through Wing Tsun’s “Sticking Hands” Practice, by Jeff Webb (Revista de Artes Marciales Asiáticas, 2012)
It was the late Bruce Lee who first demonstrated Wing Tsun gongfu’s “sticking hands” (chi-sau) exercise in the US, during the 1964 Long Beach International Karate Championships. Forty-four years later, very few outside of the art truly understand the purpose of chi-sau let alone how it develops tactile reflexes. This article will describe both the fundamental and complex methods of chi-sau training in detail. It will also explain the rationale and theories behind this method as well as discuss a variety of factors that can either improve or retard the acquisition of tactile reflexes.